2016
DOI: 10.18632/oncotarget.13839
|View full text |Cite
|
Sign up to set email alerts
|

Association between FGFR2 (rs2981582, rs2420946 and rs2981578) polymorphism and breast cancer susceptibility: a meta-analysis

Abstract: The association between fibroblast growth factor receptor 2 (FGFR2) polymorphism and breast cancer (BC) susceptibility remains inconclusive. The purpose of this systematic review was to evaluate the relationship between FGFR2 (rs2981582, rs2420946 and rs2981578) polymorphism and BC risk. PubMed, Web of science and the Cochrane Library databases were searched before October 11, 2015 to identify relevant studies. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to estimate the strength of associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
6
1
1
Order By: Relevance
“…The variant rs664677 in the DNA damage response gene ATM though not associated in our population, previously has been reported to be associated with breast cancer and lung cancer risk in Asian people [24]. Another variant rs2981582, in the FGFR2 gene, which was not associated in the population under study, was found associated with breast cancer in Asian and Caucasian population groups [25]. The gene SLC4A7 having the rs4973768 although not significantly associated with breast cancer in our population previously has been found associated with increased risk of breast cancer in Chinese population [26].…”
Section: Genetic Variants Not Associated With Bc In the Population Uncontrasting
confidence: 59%
“…The variant rs664677 in the DNA damage response gene ATM though not associated in our population, previously has been reported to be associated with breast cancer and lung cancer risk in Asian people [24]. Another variant rs2981582, in the FGFR2 gene, which was not associated in the population under study, was found associated with breast cancer in Asian and Caucasian population groups [25]. The gene SLC4A7 having the rs4973768 although not significantly associated with breast cancer in our population previously has been found associated with increased risk of breast cancer in Chinese population [26].…”
Section: Genetic Variants Not Associated With Bc In the Population Uncontrasting
confidence: 59%
“…The high expressed levels of FGFR2 in colorectal [13], lung [14], gastric [15][16][17] cancer, coding mutations [18], and more recently, FGFR fusions that lead to pathway activation [19] have been demonstrated that the FGFR2 has a signi cant oncogenic potential across multiple cancer types. ROC analysis was employed to compare the predictive accuracy of the methylation status of patients with gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, lots of studies have reported the association between rs2981578, rs2981579 and breast cancer risk in any genetic model [ 49 ]. For rs2981578, Chen et al [ 37 ] revealed that rs2981578 are associated with a decreased risk of breast cancer, which is contrary to the previous reports [ 35 , 50 ], indicating that the difference of the associations is due to different minor alleles among different ethnicities.…”
Section: Discussionmentioning
confidence: 99%